2021
DOI: 10.21203/rs.3.rs-706273/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Highly Paramagnetic Dy3+ Cations On Magnetic and Electrical Behaviour of Nanocrystalline Mnfe2o4

Abstract: In this paper, the detailed study of magnetic properties of Dy3+ substituted soft manganese ferrite (MnFe2O4) nanoparticles with varied contents of Dy3+ ions (0.00 ≤ x ≤ 0.16) was carried out by vibrating sample magnetometery (VSM) at room temperature. The synthesis of reported magnetic materials was carried out via facile wet chemical route. Structural characterization was investigated via X-ray diffraction and infra-red spectroscopy. Exploration of magnetic measurements revealed an irregular behavior in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…[185] Another report on La 3+ doped MnFe 2 O 4 nanoparticles showed that there is a decrease in the lattice parameters with an increase in La 3+ ion doping. [186] In this chapter, Sm 3+ doped MnSm x Fe 2−x O 4 nanofibers are prepared at an increasing fraction of x=0.06-0.25 (Sm 3+ ). Only a few reports from the previous literature have shown the MnFe 2 O 4 doping with various trivalent rare R 3+ earth ions (R= Pr, Nd, Eu, Gd, Tb, Pr, Ce, Y) and intriguing results were obtained for both structural and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[185] Another report on La 3+ doped MnFe 2 O 4 nanoparticles showed that there is a decrease in the lattice parameters with an increase in La 3+ ion doping. [186] In this chapter, Sm 3+ doped MnSm x Fe 2−x O 4 nanofibers are prepared at an increasing fraction of x=0.06-0.25 (Sm 3+ ). Only a few reports from the previous literature have shown the MnFe 2 O 4 doping with various trivalent rare R 3+ earth ions (R= Pr, Nd, Eu, Gd, Tb, Pr, Ce, Y) and intriguing results were obtained for both structural and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%